The impact of cost containment reforms to the Pharmaceutical Benefits Scheme (PBS) on prescribing volumes and expenditure in Australia: 1992-2011 - Lee, Kah Seng (Curtin University, 2014)
Objectives: To investigate the impact of cost containment measures on PBS prescribing volumes and expenditure. Methods: Segmented linear regression models were used to analyse the time series data from Medicare Australia’s PBS Statistics. Seven measures and four new listing dates of statins were investigated. Results: Many of the cost containment measures were effective in containing costs. Conclusions: The safety net 20 days rule was estimated to be the most effective in reducing drugs utilisation and expenditure.